Erratum to: Biomechanical comparison of graft structures in anterior cruciate ligament reconstruction (vol 25, pg 559, 2017) - Lord,BR; El-Daou,H; Sabnis,BM; Gupte,CM; Wilson,AJ; Amis,AA (Knee Surgery, Sports Traumatology, Arthroscopy, 2016)
Purpose: Double-bundle (DB) anterior cruciate ligament (ACL) reconstruction may offer kinematic restoration superior to anatomic single bundle (SB), but it remains technically challenging. The femoral attachment site has the most effect on ACL graft isometry, so a simplified three-socket (3S) construct which still uses two sockets to cover the femoral ACL attachment is attractive. It was hypothesised that ACL reconstruction using three- and four-socket techniques would more closely restore native knee kinematics compared to anatomic two-socket (SB) surgery.Methods: Nine cadaveric knees were used to evaluate the kinematics of ACL-intact, ACL-deficient, anatomic SB, three-socket, and DB arthroscopic ACL reconstructions. Suspensory fixation was used, and grafts were tensioned to match the anterior draw of the intact knee at 20°. A six-degree-of-freedom robotic system measured knee laxity under 90 N anterior tibial force and rotational laxity under 5 N-m torque. Combined moments were applied to simulate the pivot-shift subluxation: 4 N-m internal rotation and 8 N-m valgus.Results: Significant differences between reconstructions were not found during anterior tibial loading, apart from SB being more lax than DB at 60° flexion. All reconstructions produced comparable laxity to the intact state, apart from SB at 60°. Significant differences between reconstructions were not found at any flexion angle during tibial internal/external applied torques. Under combined loading, DB produced significantly less laxity than SB constructs apart from anterior tibial translation at 0° and internal rotation at 45°. 3S and DB were comparable to the native knee throughout.Conclusion: Although 3S restored laxities to a similar extent to DB, significant superiority over SB surgery was not observed. Although statistically significant differences were found between SB and DB surgery during anterior tibial and simulated pivot-shift loading, both remained similar to the nativ